Stereotypization and mythologization of the image of Russia in modern Spanish newspapers - Alexander S. Oleynikov; Valentina A. Slavina (RUDN Journal of Studies in Literature and Journalism, 2019)
The article discusses the stereotyping and mythologization of the image of Russia, identified as a result of an analysis of the modern Spanish press. The empirical base of the study consists of articles of electronic versions of socio-political newspapers “ABC”, “El Pais”, “El Mundo” from 2014 to 2018. The considered time interval is associated with significant changes in international relations and the emergence of differences between the West and Russia on key issues of its foreign and domestic policy. Immediate response of the international community to the actions of Russia has contributed to fundamental changes in its perceptions about the global media space. An important component of the image of the world in the media sphere is the image of the state, which is created primarily through the media. It is formed on the basis of actual events of the surrounding reality, reflects their dynamics, expresses the public consciousness and influences it. Creating a media image of Russia, Spanish newspapers rely on stereotypical ideas and myths about it existing in the West, and also take part in the creation of new ones. Stereotyping and mythologization form a specific negative perception matrix, which negatively affects the image of Russia and demonizes it.